5.6x-5.1=1.06

Simple and best practice solution for 5.6x-5.1=1.06 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.6x-5.1=1.06 equation:


Simplifying
5.6x + -5.1 = 1.06

Reorder the terms:
-5.1 + 5.6x = 1.06

Solving
-5.1 + 5.6x = 1.06

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5.1' to each side of the equation.
-5.1 + 5.1 + 5.6x = 1.06 + 5.1

Combine like terms: -5.1 + 5.1 = 0.0
0.0 + 5.6x = 1.06 + 5.1
5.6x = 1.06 + 5.1

Combine like terms: 1.06 + 5.1 = 6.16
5.6x = 6.16

Divide each side by '5.6'.
x = 1.1

Simplifying
x = 1.1

See similar equations:

| (7y^2-4y+1)(8y^2-6y)= | | [-6]= | | 4/5y+7/y-2 | | 2x-5=-55 | | -9(5)= | | 6X-19=89 | | x/-7=-21 | | -12-(-9)= | | h=-16t^2+117.5t+0 | | x/-7=21 | | 2(5/7)(-3/8) | | 14-6x+10-2x=x-11x | | 4x-2y=z | | -8P+9=25 | | -2x-18+3x=-4 | | x^(1/2)=7 | | 63xpi= | | D/-5-6=20 | | 4x^2-3x=(16x-12)/x | | 3.5/9=x/27 | | 22-5C=-8 | | x+7=7x-41 | | T/3+4=-5 | | 6t-11=3t-2 | | -2a+2+3a=8-29 | | X+(-35)=98 | | 7-6p=10 | | 5-y=25 | | 2k-0.5=17.85 | | -1/5*5 | | X-67=167 | | 3n+1.7=5 |

Equations solver categories